Electrical performance and use in logic of printed current switching transistors employing nanostructured silicon - Zambou, Serges (Department of Physics, 2017)
Printed electronics seek to replace a full range of conventional electronic components and circuits with their printed counterparts, and offer an extraordinary range of advantages in producing exible, low-cost, large area coverage, stretchable, wearable devices and circuits. We already witness the incredible advantages and extraordinary contribution of printed electronics in our daily lives, as well as in the cutting-edge printed electronics innovations and research available today. At an in-depth level, and as an important contribution to printed devices, this work presents the design, production, and characterization of a novel fully printed current-driven switch, referred to here as a Current Switching Transistor (CST). The CST possesses the unique ability to operate as a two-way switch for both direct (DC) and alternating current (AC). In this thesis, CSTs were successfully used for the fabrication of exible fundamental "AND" and "OR" logic gates. At the fundamental level, this work sets out to illustrate that, a printed nanostructured silicon layer could be used as the active material for current switching transistors and other electronic devices. Also investigated was the temperature dependence of the transfer characteristics, in an extended range of temperature from 340 to 10 K, as well as their reliability when subjected to a constant current bias stress. Significantly in this work, the switching behavior observed and the electrical properties of the CSTs produced using nanostructured silicon remained excellent at temperatures as low as 10 K. Such transistor performance demonstrates the transistor's high potential as the candidate for cryogenic applications. The transistor's mechanism of operation was shown to be based on the activated percolation of charge carriers through the network of particles in the active silicon layer. Additionally, this work shows that the ON/OFF ratio of the transistors was temperature dependent, yielding the highest value of 10³ achieved at cryogenic temperatures below 150 K. A reliability test achieved through bias stressing the base terminal, with a constant voltage of 52 V or a current of 75 μA for up to 6 hours at room temperature proved the devices to be highly stable. Except for the reversible shift in the switching voltage, which could be attributed to self-heating, no alteration of the device characteristics was observed.